The putative arthritogenic cationic 19-kilodalton antigen of Yersinia enterocolitica is a urease beta-subunit. - Skurnik, M (1993)
The gene coding for a putative 19-kDa arthritogenic antigen of Yersinia enterocolitica O:3 (A. K. H. Mertz et al., J. Clin. Invest. 87:632-642, 1991) was cloned and sequenced after amplification of part of the gene by the polymerase chain reaction using degenerate primers, inferred from the amino acid sequence. The deduced amino acid sequence of the antigen showed similarity to small subunits of ureases from several different organisms, including the jack bean urease. Screening of a genomic library of Y. enterocolitica O:3 with a 19-kDa-antigen-specific DNA probe allowed recombinant clones containing the entire urease operon to be obtained. These clones expressed urease activity in Escherichia coli.